2002
DOI: 10.1111/j.1834-7819.2002.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries experience of preschool children from the north brisbane region

Abstract: Background: To report the dental caries experience of preschool children within the north Brisbane region and to investigate the association between selected social and demographic variables and disease presence. Methods: A cross-sectional sample of 2515 children aged four to six years was examined in a preschool setting using decayed, missing, filled teeth/surface (dmft/dmfs) and percentage caries free indices. A self-administered questionnaire obtained information regarding selected social and demographic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 10 publications
4
51
2
2
Order By: Relevance
“…In the study conducted by Hashim et al (14) the prevalence of dental caries in preschool children of United Arab Emirates was about 76.1%. In a similar study conducted in Uganda (15), it was 62%, and in a study conducted by Nanayakkara et al in Sri Lanka, the prevalence of dental caries in preschool children was equal to 72% (16). In this study, the mean quality of life for children was obtained as equal to 10.94 ± 7.67, which was lower compared with similar studies.…”
Section: Discussioncontrasting
confidence: 46%
“…In the study conducted by Hashim et al (14) the prevalence of dental caries in preschool children of United Arab Emirates was about 76.1%. In a similar study conducted in Uganda (15), it was 62%, and in a study conducted by Nanayakkara et al in Sri Lanka, the prevalence of dental caries in preschool children was equal to 72% (16). In this study, the mean quality of life for children was obtained as equal to 10.94 ± 7.67, which was lower compared with similar studies.…”
Section: Discussioncontrasting
confidence: 46%
“…15,31 Approximately 20% of infants are at high risk of dental caries within the first two years of life and have poorly controlled feeding behaviours, resulting in the initiation of early childhood caries before two years of age. 28,32,33 As mentioned previously, risk status can quickly change over time. In terms of caries risk, the onset of a chronic medical condition, a change in family social circumstances and a change in either controlled dietary or oral hygiene practice when a young adult leaves the parental home can quickly increase the risk of future caries development.…”
Section: Caries Predictionmentioning
confidence: 96%
“…4 Another Melbourne study that reported an eightfold difference in levels of tooth decay between preschoolers of Lebanese and Anglo-Saxon backgrounds found that maternal education explained 23 per cent of the variation in disease. 5 A study of children aged four to six years living in northern Brisbane identified non-Caucasian ethnicity, family language other than English, low socio-economic status 6 and single parent status 7 as sociodemographic risk factors and behavioural risk factors of sleeping with a bottle and sipping from a bottle. Breast-feeding between three and 12 months of age was protective.…”
Section: S C I E N T I F I C a Rt I C L Ementioning
confidence: 99%